Challenges facing woment leaders in local government: a case study of the City of Johannesburg - Letlape, Lulama (My University, 2011)
There are many key issues arising from the debates around the transformation of South Africa. One of these has to do with gender and women's issues. Since the onset of the democratic dispensation in South Africa, issues about women and gender have assumed greater prominence than ever before. The result of this development has been the appointmnet of many women in leadership positions in business and politics.Local governemnt is important in the development of South Africa. The implementation of government's economic and socail policies happens at this level. Therefore, communities that are supposed to be served are adversely affected by poor performance in service delivery by local government. Leadership and management at local government level are therefore crucial as they determine the progress of local communities and the development of the country as a whole. Local government employees have to meet these high expectations and enormous demands, especially those in leadership positions.... The researcher discovered that there is a need for a further study into the perceptions of women (concerning) the 50/50 women represnetation campaign in local government. This is as a result of the reluctance of women leaders to see themselves as beneficiaries of this campaign. Most of the women leaders did not want to acknowledge the fact they are in leadership positions because of the gender quota but preferred to see themselves equally as qualified as men to hold the positions they are holding. This means therefore that women avoid seeking special support or acknowledging existing support. It can be deducted from the study that women in local government do face leadership challenges yet they do not openly acknowledge these challenges as they want to see them as generic leadership challenges that can be faced by men as well.
MM - P&DM
Keywords: Local authorities; Leadership; Women in leadership